2002
DOI: 10.1108/00070700210418767
|View full text |Cite
|
Sign up to set email alerts
|

Women, men and food: the significance of gender for nutritional attitudes and choices

Abstract: This article reports the results of the re-analysis of a substantial set of survey based quantitative data relating to food beliefs, practices and preferences. The particular focus of attention was upon gender contrasts. Several statistically significant differences between men and women were identified. These differences occurred in such areas as views on food and health, the ethical dimensions of food production and food selection, nutritional attitudes and choices, dietary change, food work and body image. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
174
2
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(224 citation statements)
references
References 20 publications
24
174
2
14
Order By: Relevance
“…In a similar way, the current study shows how an 'ill--health' context can both challenge and sustain previous empirical findings that men have a 'less worried' stance toward food and are more likely to 'just eat what they like' (Beardsworth et al, 2002). The situation for many men in the current study is that they do, understandably, begin to show more interest in food following prostate cancer diagnosis yet often not to the extent that they would allow it to become too central in their lives or to interfere with the enjoyment of particular life activities; that is, most still view moderation and 'treats' in dietary choices as an important part of 'balance' in their lives.…”
Section: Discussionsupporting
confidence: 52%
“…In a similar way, the current study shows how an 'ill--health' context can both challenge and sustain previous empirical findings that men have a 'less worried' stance toward food and are more likely to 'just eat what they like' (Beardsworth et al, 2002). The situation for many men in the current study is that they do, understandably, begin to show more interest in food following prostate cancer diagnosis yet often not to the extent that they would allow it to become too central in their lives or to interfere with the enjoyment of particular life activities; that is, most still view moderation and 'treats' in dietary choices as an important part of 'balance' in their lives.…”
Section: Discussionsupporting
confidence: 52%
“…This is consistent with the literature, which has found that women generally view their diet as more important to their health than do men . In addition, women have greater responsibility for family health and still commonly assume the traditional role of household food purchasers and 'gatekeepers' (Worsley and Worsley, 1989;Beardsworth et al, 2002). The findings show that around a third of men (in contrast to 10% of women) do not make their own decisions about the food they eat.…”
Section: Discussionmentioning
confidence: 74%
“…This scene critiques the gendered view of dietary habits in the Western world, most notably, the feminization of veganism (often noted in previous research) [17,22,24,31]. Esselstyn's statement directly challenges the idea that eating meat means being masculine, and contrastingly argues that eating plants is masculine.…”
Section: Vegan Rejoinders To Mainstream Criticismsmentioning
confidence: 99%